Psychological factors may affect the quality of life in irritable bowel syndrome patients more than the gut itself? A multicenter cross‐sectional study - Xiaotian Xie; Jing He; Shu Xu; Zhiyue Xu; Yanqin Long; Zhijun Duan; Jie Yang; Zhifeng Zhang; Jun Wu; Lianying Cai; Liexin Liang; Ning Dai; et al. (JGH Open, 2024)
Abstract Background and Aim Both intestinal symptoms and comorbidities exist in irritable bowel syndrome (IBS) patients and influence their quality of life (QOL). More research is needed to determine how these variables impact the QOL of IBS patients. This study aimed to determine which specific factors had a higher influence on QOL and to further compare the effects of intestinal symptoms and comorbidities on QOL. Methods IBS patients were recruited from six tertiary hospitals in different regions of China. QOL, gastrointestinal symptoms, and comorbidities were assessed by different scales. Correlation analysis, multiple linear regression, and mediation model were used for statistics. Results Four hundred fifty‐three IBS patients (39.7% women, mean age 45 years) were included and no significant differences in QOL were found across demographic characteristics. Abnormal defecation (r = −0.398), fatigue (r = −0.266), and weakness (r = −0.286) were found to show higher correlation with QOL. More than 40% of IBS patients were found to suffer from varying degrees of anxiety or depression, and anxiety (r = −0.564) and depression (r = −0.411) were significantly negatively correlated with QOL (P < 0.001). Psychological factors showed the strongest impact (β′ = −0.451) and play a strong mediating role in the impact of physiological symptoms on QOL. Anxiety was found to be the strongest factor (β′ = −0.421). Conclusion Compared with other symptoms, psychological symptoms, particularly anxiety, are more common and have a more negative influence on QOL. The QOL of IBS patients is also significantly impacted by abnormal defecation, abdominal distension, and systemic extraintestinal somatic symptoms. In the treatment of IBS patients with unhealthy mental status, psychotherapy might be prioritized.